Territory and ontology in the educational practices of an indigenous Zapotecan community in Mexico - Raquel Aparicio Cid (Environmental Association of Southern Africa, 2019)
This paper is inscribed within the study of social educational practices in rural indigenous communities of Mesoamerica, practices through which the store of knowledge that guides relationships with the environment are recreated. Ethnographical research conducted in a Zapotec community in the state of Oaxaca, southern Mexico, shows that communitarian educational practices form an everyday cognitive-axiological framework through which the norms of coexistence and social organisation are assimilated. The underlying purpose of these practices is to promote the historical and cultural continuity of the collective based on a reciprocal relationship with the environment, which is their home and the source of their well-being and biocultural identity. The resilience of this population lies in their use of socio-historical learning to renew their organisational structures, with the purpose of facing the challenges posed by civilisation. This paper describes aspects of these historical learnings and current social educational practices, as well as their ontological principles.